PENGARUH PENAMBAHAN KALIUM IODAT (KIO3) TERHADAP KADAR IODIUM, KADAR AIR, pH, DAN WARNA KUNING TELUR PADA TELUR ASIN - suryo pratomo unggul yudho; Imam Thohari; Agus Susilo (MaduRanch: Jurnal Ilmu-Ilmu Peternakan, 2017)
The purpose of this research was to find the cocentration of potassium iodate (KIO3 ) on salted yolk eggs characteristics iodium content, moisture content, pH, and colour. The material that used in this research were duck eggs, salt, potassium iodate (KIO3 ), bricks powder, and water. The method used experiment research using Completely Randomized Design (CRD) with 5 treatments and 3 replications. The concentration of potassium iodate (KIO3 ) addition that used as treatments were P0 (0ppm), P1 (500ppm), P2 (1000ppm), P3 (1500ppm), and P4 (2000ppm). Data were acquired and processed using Microsoft Excel, then were analyzed with analysis of variance (ANOVA), there were signifcantly influence continued by Duncan’s Multiple Range Test (DMRT). Result of this research showed that there was no iodium that was detected in salted yolk eggs ini any treatments, concentration of potassium iodate (KIO3 ) give a significant effect (P<0.01) on colour intensity b* (yellowness), significant (P<0.05) on colour intensity a* (redness), but didn’t give different effect (P>0.05) on moisture content, pH, and colour intensity L* (lightness) of salted yolk eggs. The conclusion is adding of potassium iodate (KIO3 ) on salted yolk eggs showed didn’t give a efficient result because there was no iodium that was detected in salted yolk eggs. Based on the research results, there should be more research on the quality of salted egg that gets the addition of potassium iodate (KIO3) with the different test methods and different media of dough salted eggs dressing.